Cecília e Ronald: conversas transversas com Pessoa - Dal Farra, Maria Lúcia (Navegações, 2013)
A obra de Cecília Meireles, de um lado, e a de Ronald de Carvalho, de outro, parecem ter entrado em locução com a obra de Pessoa, assimilada de maneira diversa por cada um deles. Cecília, organizadora da primeira antologia brasileira onde Pessoa é privilegiado, foi acusada por Agripino Grieco de ter seguido “simiescamente” o Poeta português. Ronald não sofreu tal pecha e parece, ao contrário, ter quase ignorado Pessoa, ou (por uma razão insuspeitável) ter evitado divulgá-lo no Brasil. Este artigo procura investigar pistas e especular algumas suspeitas respeito.” ..................................................................... Cecília e Ronald: a dialog with Pessoa Abstract: The work of Cecilia Meireles on one hand, and Ronald de Carvalho on the other, seem to have entered in a dialog with Pessoa, though assimilated differently by each one of them. Cecilia, organizer of the first Brazilian anthology where Pessoa is privileged, was accused by Agripino Grieco of literally mimicking the Portuguese poet. Ronald suffered no such taint and seems, instead, to have almost ignored Pessoa’s work, or (for an unsuspected reason) decided to avoid releasing it in Brazil. This article intended to investigate some clues and speculate about some possible reasons about this. Keywords: Brazilian and Portuguese poetry; Literary interference; Modernism.